HAND AND WRIST PAIN - Izza Ayudia Hakim; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2022)
Hand and wrist disorder affects a patient’s overall well-being and health-status. Epidemiology of elbow pain and pain per year in 58 of 10,000 patients in the UK, and is the fourth most common musculoskeletal site in the upper extremity after the shoulder, hand and. Characteristics of pain that can arise in the form of pain isuch ias radiating, tingling, thick feeling and can be in the form of weakness when gripping. This can happen because of a movement that is not appropriate and occurs repeatedly. There is a special physical examination that can support a diagnosis of pain in the hands and hands. The therapy used initially is non-steroidal anti-pain, even if it cannot be resolved, corticosteroid injections can be given to the painful area. Keyword : hand and wrist pain, pain, upper extremity pain